Development and implementation of an 84‐channel matrix gradient coil. Issue 2 (25th April 2017) - Littin, Sebastian; Jia, Feng; Layton, Kelvin J.; Kroboth, Stefan; Yu, Huijun; Hennig, Jürgen; Zaitsev, Maxim
Abstract : Purpose: Design, implement, integrate, and characterize a customized coil system that allows for generating spatial encoding magnetic fields (SEMs) in a highly‐flexible fashion. Methods: A gradient coil with a high number of individual elements was designed. Dimensions of the coil were chosen to mimic a whole‐body gradient system, scaled down to a head insert. Mechanical shape and wire layout of each element were optimized to increase the local gradient strength while minimizing eddy current effects and simultaneously considering manufacturing constraints. Results: Resulting wire layout and mechanical design is presented. A prototype matrix gradient coil with 12 × 7 = 84 elements consisting of two element types was realized and characterized. Measured eddy currents are <1% of the original field. The coil is shown to be capable of creating nonlinear, and linear SEMs. In a DSV of 0.22 m gradient strengths between 24 mT∕m and 78 mT∕m could be realized locally with maximum currents of 150 A. Initial proof‐of‐concept imaging experiments using linear and nonlinear encoding fields are demonstrated. Conclusion: A shielded matrix gradient coil setup capable of generating encoding fields in a highly‐flexible manner was designed and implemented. The presented setup is expected to serve as a basis for validating novel imaging techniques that rely on nonlinear spatial encoding fields. Magn Reson Med 79:1181–1191, 2018. © 2017 International Society for Magnetic Resonance in Medicine.